THE LIVED EXPERIENCE OF NURSES WHO ENCOUNTER THE UNEXPECTED DEATH OF A PATIENT - Mumbrue, Teresa L. (My University, 2010)
Nurses are the primary caregivers for patients while in the hospital. Regrettably, stable patients often experience complications that were otherwise unanticipated. Often times, patients die and the nurse is left to cope alone and try to understand the emotional stirrings that are often unsettling. While many studies focus on improving patient quality of care provided by the nurse, few, if any, examine the nurse and the perspective they may have on the dynamic healthcare environment and unexpected patient deaths. Grief is common among nurses and is often heartfelt when a patient dies, but that grief is often ignored (Brosche, 2007). The negative impact of this phenomenon may lead to nurses experiencing moral issues, specifically moral distress as well as compassion fatigue. The emotional reaction of nurses who experience a patient?s death that was unexpected has largely been unexamined. The purpose of this study is to describe the lived experience of nurses who care for patients who unexpectedly die. The research question is; what is the lived experience of nurses who encounter the unexpected death of a patient? The theoretical framework that provides the foundation for this study is Lazarus' theory of stress, coping and adaptation along with Spiegelberg's approach to understanding phenomenon as lived by the person experiencing the phenomenon. A naturalistic paradigm coupled with a descriptive phenomenological approach was used in order to describe the meaning of the experience many nurses face when exposed to patients deaths. The participants for this study are nurses that are currently employed in a hospital setting and have experienced this phenomenon. Data analysis consisted of Spiegelberg's method of interpretation of the qualitative data.
A Clinical Paper Submitted In Partial Fulfillment of the Requirements For the Degree of Master of Science in Nursing Family Nurse Practitioner
Keywords: Death psychological aspects; Nursing psychological aspects; Hospital patients mortality; Nurse and patient